Inuit identities in Montreal, Canada - Kishigami, Nobuhiro (Études/Inuit/Studies, 2002)
AbstractAs Dorais (1994) has indicated, the distinction between the concepts of cultural and ethnic identities are important for us to understand the identities of contemporary Canadian Inuit Although the Inuit themselves do not distinguish between these identities, I consider them to be useful analytical concepts. I argue that cultural identity is a tool for an Inuk to live with his fellow Inuit in daily life and that ethnic identity is a political tool especially for both urban and arctic Inuit to deal with others in multi-ethnic situations.